Application with an Event Time Distribution on Spatial Process - Onyemachi, Chris Uchechi (Transactions on Engineering and Computing Sciences, 2024)
The use of models in sciences to describe phenomena that assume non negative values such as size distributions, flood frequencies, radio wave amplitude fluctuations, air velocity fluctuations and geographical analysis are enhanced with the lognormal distribution, and the likes of Weibull and Exponential distributions as a life time distribution model. In most cases, these are empirically observed and test fits and often other models such as gamma distribution are also fitted. The distribution is specified by saying that the life time of random variable X is lognormal if the logarithm Y = In X of the life time is normally distributed with mean μ and variance σ2. The two parameter lognormal distribution denoted by ; with the corresponding normal distribution is considered. Lognormal distributions play a central role in human and ecological risk association, its probability plots are invaluable because they provide a powerful way to visualize measured data or simulated results such as in landslides.